Aldous Huxley’s Poetry of Silence - Shadurski, Maxim (Respectus Philologicus, 2012)
Utopian thought, conventionally seeking to harmonize the world, witnessed an essential revision in the 20th century. This period of grand political and social upheavals, world wars, an arms race, scientific and technological progress, ecological concerns, and globalization radically undermined mankind’s faith in the humanistic potential of utopian projects. However, in Aldous Huxley’s writings, the intention to summon up a utopian experiment superseded any agonies of doubt about programmes of social reconstruction. Huxley turned to utopia when mass distrust in the constructive impulse of the genre had become notable in the socio-cultural climate. In Huxley’s last novel, Island (1962), “the poetry of silence” can be seen to render an optimistic response to the unholy state of the world.This article examines the novel’s lyrical interspersions, which arguably create a specific concept of silence through a series of thematic explorations comprising the ideas of noiselessness, speechlessness, and peace. The idea of noiselessness endorses a form of overcoming the world’s invincible cacophony. This kind of omnipotent dissonance can be diminished only by a supernatural power which integrates man’s disparate relationships with the universe. Like Nature for Wordsworth, Huxley’s image of the noiseless movement of the world unveils an image of unity to those who bring with them “a heart that watches and receives.” The idea of speechlessness surfaces in the lyrical fragments of the novel that touch upon intuition. Intuitive discoveries lie at the heart of a religion unfettered from dogma, and allow access to the perennial wisdom which becomes “suddenly visible” through the act of elevation to the summit of the universe. The idea of peace is placed outside the conventional frame of existential discrepancies. For this reason, the image of Shiva is meant to transcend the opposition of life and death. As long as Shiva dances simultaneously in all the planes of reality, the Palanese can learn from him how to exist in non-attachment. The acceptance of the world’s entropic progression checked by the poetry of silence leads the protagonist to a spiritual awakening and stirs his empathy for the utopian order realized in Pala.The poetry of silence embraces the beauty of the world which comes into existence from what Huxley calls a “pregnant emptiness.” The mystery of this creation cannot be subjected to any scientific, philosophical, or even theological systems of reference. One may only sense this mystery without reasoning. Wisdom converges with the skyin emptiness, dubbed “the womb of love,” and creates a universe from the poetry of silence. In Island, utopian thought, traditionally focusing on the regular patterns of a perfect society and state, attains a mystical profile promoted by the poetry of silence.
Keywords: utopia; poetry of silence; social reconstruction; mysticism; world wisdom